OC-048 Trans-anal Submucosal Endoscopic Resection (taser): A New Endo-surgical Approach To The Resection Of Giant Rectal Lesions. (9th June 2014) - Tsiamoulos, ZP; Warusavitarne, J; Elliott, T; Saunders, BP
Abstract : Introduction: Trans-anal surgical (TEMS/TAMIS) and advanced endoscopic resection (ESD, P-EMR) procedures have the potential to provide complete and successful eradication of giant rectal polyps. Both approaches however have limitations in terms of practicality and safety. We describe a new endo-surgery technique called Trans-Anal Submucosal Endoscopic Resection (TASER) which combines the advantages of both the endoscopic and transanal surgical approach. Methods: The GelPoint Path trans-anal access port allows simultaneous passage of an endoscope and two laparoscopic retractors. Working with the endoscopic image the laparoscopic retractors (Johen 33 mm forceps) allow dynamic tissue retraction to facilitate endoscopic dissection (Flush knife–BT) or snare placement (Olympus snare master/spiral snare). All procedures were performed under general anaesthesia and with patients in the lithotomy position. Results: Eleven patients (mean age 55 years, 3 male/8 female) underwent TASER for 11 lesions, distributed from the lower rectum to the recto-sigmoid junction and with a median size of 85 mm, range 40–180 mm. Polyp morphology was (3/11 flat (Paris 2a), 4/11 sessile (Paris 1s) and 4/11 mixed type (Paris 2a+1s). In all cases a circumferential mucosal incision was made and histology confirmed free lateral margins in all cases. 10/11 rectal polyps were adenomatous and one had a small focus of moderate differentiated adenocarcinoma (incomplete local excision). Complete endoscopic excision in a single session was achieved in 10/11 cases (91%). Median completion time of the procedure was 215 min, range 120–480 min. Tissue retraction was used in every case and resection was completed by ESD alone (4/11), ESD + EMR (4/11) ESD + EMR + trans-anal surgical excision (3/11). Intra-procedural bleeding occurred in 8 cases, controlled with hemostatic clips and Coagrasper (Olympus); surgical suturing was required in one case (1/8). Prophylactic clips (2/11) and surgical sutures (1/11) were placed to treat deep muscle injury. There were no perforations and no delayed bleeding episodes. Patients were discharged the day following TASER in all cases. Surveillance at 3–6 months revealed no recurrence in 6 cases, whereas in four cases the follow up procedure is still pending. The malignant polyp case was referred to surgery with a good clinical outcome (T3, N0, M0). Conclusion: TASER appears to be a safe and efficient approach providing an optimal platform for resection of large rectal lesions. In our experience it provides the optimal platform for the minimally-invasive management of these high risk lesions. Disclosure of Interest: None Declared.